Trends and dilemmas of the current context towards the construction of a prospective look: cooperatives in Latin America and the Caribbean - Li Bonilla, Federico; Coto Moya, Luís Guillermo (Cooperativismo & Desarrollo, 2023)
Contemporary society is undergoing changes of multiple varieties; The understanding of different social phenomena requires the construction of new references of knowledge, which help to decipher the dimension, scope and depth of social changes. For the rigorous study of social phenomena, the search and construction of new conceptual and methodological bases is required, as well as acute and critical observation by scientists of social practice, which allows the generation of new sources of knowledge. In this area, it is important to evaluate the role of a strategic actor in contemporary society; Cooperativism represents a socio-business sector with a presence of almost a century of contemporary history, in most Latin American countries. One of the areas, among others, that has been experiencing important changes in the new context, is that which refers to the world of organizations; from a conception in its beginnings, of a "bipolar" nature, which defined companies as public and private, to a new reality, where new organizations appear that wander between the public and the private, between the social and the particular, between property public and private property, between participatory and representative democracy, between private interests and collective interests. It is in this framework that the organizations of the social solidarity economy appear, a concept that is as broad as it is discreet, concrete and sometimes diffuse, with little-known identities, nature and limits, where a diverse range of valuations and appreciations about its nature proliferate. , as well as their contribution to society. This article intends to delve into the analysis of the role of cooperativism in society, trying to glimpse through a prospective vision where to direct the main strategic actions.